Diagnosis of alcohol misuse and alcoholic liver disease among patients in the medical emergency admission service of a large urban hospital in Sub-Saharan Africa; a cross sectional study - Kenneth Opio, Christopher; Seremba, Emmanuel; Ocama, Ponciano; Lalitha, Rejani; Kagimu, Magid; Martens Lee, William (Pan African Medical Journal, 2013)
Uganda is among the top ten consumers of alcohol worldwide though there is little data on alcohol related liver disease. We describe alcohol use, alcohol misuse, and alcoholic liver disease among adults at the emergency admission service of a large urban hospital in Uganda. Methods: All adults who consented were prospectively evaluated for alcohol use by inquiry and alcohol misuse by the "Cutting down, Annoyance, Guilt and Eye-opener- CAGE" questionnaire. Alcohol related hepatocellular liver injury was assessed using aspartate aminotransferase, and alanine aminotransferase levels. A combination of CAGE score ≥2 and De Ritis ratio ≥2 defined alcoholic liver disease (ALD). Human Immunodeficiency Virus (HIV), and viral hepatitis B and C serologies were evaluated in all the patients. Descriptive and inferential statistics were generated to answer our research questions. Results: Three hundred and eighty individuals consented and participated in the study. Among these, 46.8% acknowledged use of alcohol while 21% and 10% met the study definition of alcoholic misuse and alcoholic liver disease respectively. Both alcohol misuse and alcoholic liver disease was significantly associated (p-value ≤ 0.05) with male gender, region of origin, number of life time sexual partners and serum albumin below 3.5 mg/dl after univariate and multivariate analysis. Conclusion: Alcohol misuse and alcoholic liver disease is frequent in this medical emergency unit. Our study suggests a link between alcohol misuse or alcoholic liver disease and male gender, region of origin, number of sexual partners, and serum albumin below 3.5mg/dl.
Keywords: Alcohol use; Alcohol misuse; Alcoholic liver disease; Aspartate aminotransferase; Alanine aminotransferase; CAGE questionnaire; De Ritis ratio